2002
DOI: 10.1182/blood.v100.2.677
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of HTLV-I in blood components after leukocyte depletion

Abstract: The human T-cell leukemia virus HTLV-I is a transfusion-transmissible retrovirus targeting T lymphocytes for which screening is not currently undertaken in United Kingdom blood donors. The introduction of universal leukocyte depletion (LD) of the United Kingdom blood supply raises the question as to the degree of protection afforded by this procedure against HTLV-I transmission by blood components. HTLV-I viral DNA removal by leukocyte-depleting filters was assessed in units of whole blood and platelets by rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 30 publications
2
27
0
2
Order By: Relevance
“…Evidence for possible monocyte activation comes from recent observations reporting cytokine production by PBMCs exposed to CMV for only 18 hours, a CD14-dependent phenomenon. 20 The less efficient removal of CMV by platelet than by whole blood filtration was also found with HTLV, 12 although one study of filtration and centrifugal apheresis LD achieved approximately 3 10 log CMV removal. 11 We noted greater plasma contamination associated with reduced viral recovery from filters with platelet LD, raising the possibility of CMV release from leukocyte cytoplasm 21 during filtration.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Evidence for possible monocyte activation comes from recent observations reporting cytokine production by PBMCs exposed to CMV for only 18 hours, a CD14-dependent phenomenon. 20 The less efficient removal of CMV by platelet than by whole blood filtration was also found with HTLV, 12 although one study of filtration and centrifugal apheresis LD achieved approximately 3 10 log CMV removal. 11 We noted greater plasma contamination associated with reduced viral recovery from filters with platelet LD, raising the possibility of CMV release from leukocyte cytoplasm 21 during filtration.…”
Section: Resultsmentioning
confidence: 98%
“…We have previously used infected T lymphocytes and real-time PCR to assess human T-cell leukemia virus-I (HTLV-I) removal by LD. 12 A CMV-infected T-cell line has also been described to measure CMV removal, 13 but T cells are not a major physiological reservoir of CMV. We have therefore modified a previously described system 14 to generate CMV-infected mononuclear cells, including CD14 ϩ monocytes, for spiking into blood donations prior to LD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar situation exists for HTLVI and HTLVII. One experiment demonstrated that, following leukocyte depletion, HTLVI proviral DNA remained detectable (albeit at reduced levels) in 13 of 16 whole blood samples, all filtered platelets spiked with MT-2 cells, and in blood from 3 of 5 asymptomatic HTLVI carriers (the infectivity of the filtered components is not known) [47]. [48].…”
Section: Leukocytes and Latent Virusesmentioning
confidence: 99%
“…EBV titers are also significantly reduced by RBC filtration, rendering most filtered units EBV-negative [28] . HTLV-I titers decline as well after LR, though not completely [29] . Other blood borne infectious diseases curbed by RBC filtration include malaria, leishmaniasis, human granulocytic anaplasmosis, and Yersinia enterocolitis [3033] .…”
Section: Introductionmentioning
confidence: 99%